Director departure following political ideology (in)congruence with an incoming CEO - Busenbark, John R.; Bundy, Jonathan; Chin, M.K. (Strategic Management Journal, 2023)
Abstract Research Summary Political ideologies play a critical role in how individuals view the world and their social interactions. Management scholars have theorized about how executives' politics may influence their firms' activities, but organizational research has not yet fully embraced the political science logic that bidirectional ideological alignment is perhaps the most influential factor in crafting social circles. We incorporate this perspective by theorizing about how political ideology (in)congruence between an incoming CEO and directors impacts whether those directors retain their seat or depart from the board. Coalescing political research with the socio‐behavioral view of directorships, we argue that ideological incongruence is related to departure and congruence enhances retention. In post hoc analyses, we also uncover preliminary evidence that the salience of ideological incongruence supersedes congruence in director departure. Managerial Summary Executives' political ideologies have a profound impact on the organization, so it is imperative to understand whether the political views of those in the upper echelons play a role in cultivating who sits at the apex of the firm. In this study, we find that directors are inclined to remain on the board when they share a political ideology with an incoming CEO, but that they are also apt to depart from their positions when their political views do not align with the incoming CEO. In intriguing quantitative analyses, we also unearth that, like most individuals in society, directors are perhaps more repelled by a CEO with an opposing political ideology than they are attracted to a CEO with similar political leanings.